Comparative Evaluation of Seismic Response and Structural Performance of Two-Story Building Using Equivalent Static and Response Spectrum Methods - Midia Rahma; Zikra Fauzan Virawan; Mahdika Putra Nanda; Ina Asha Nurjanah (Jurnal Fondasi, 2026)
Seismic response analysis of building structures is essential, as different analytical approaches may produce varying predictions of structural behavior under earthquake loading. This study aims to compare the seismic response of a two-story building using two linear analysis methods, namely equivalent static analysis and response spectrum-based dynamic analysis. A three-dimensional structural model was developed using structural analysis software to evaluate key parameters, including natural period, base shear, and inter-story drift. The results indicate that the dynamic analysis produces higher base shear and lateral displacement compared to the static method. These differences suggest that the dynamic approach is more capable of representing realistic structural behavior by accounting for natural vibration characteristics and spectral acceleration. The findings highlight that dynamic effects play a significant role in determining structural response, even for low-rise buildings. Therefore, the application of dynamic analysis is recommended to improve the accuracy of seismic performance evaluation and structural design.